Human security in South Asia concept, environment and development - Subramanyam Raju, A. (Routledge, 2020)
"This book delves into the theory and praxis of human security in South Asia. Home to almost a quarter of the world's population and fast emerging markets, South Asia holds social, geo-political, and economic significance in the current global context. The essays in the volume: examine the challenges to human security through an exploration of environmental issues including water availability, electric waste, environmental governance, and climate change; explore key themes such as development, displacement and migration, the role of civil society, sustainable development, and poverty discuss developmental issues in South Asia and provides a holistic picture of non-military security issues. Bringing together scholars from varied disciplines, this comprehensive volume will be useful for researchers, teachers and students of international relations, human rights, political science, development studies, human geography and demography, defence and strategic studies, migration and diaspora studies, and South Asian studies"--